CO2 Rich Streams Methanization Intensified by Steam Adsorption with LTA Zeolites in Fluidized Bed Reactor - De Matías De la Rúa, Irene; Sanz-Martínez, Andrés; Mercader, Victor; Durán, Paul; Francés, Eva; Herguido, Javier; Peña, José Ángel (Jornada de Jóvenes Investigadores del I3A, 2022)
The Sabatier reaction enhanced by selective water sorption (SESaR process), was evaluated in a fluidized bed reactor. This constitutes a configuration alternative to the traditional fixed bed one. A Ni-Fe bimetallic catalyst (Al2O3 as support) and zeolite 5A as adsorbent were used.